Study of critical exponents in doped La2/3Ca1/3Mn1-yFe yO3(y = 0, 0.03) manganite films (2014)
In this work, we investigated close to the Curie temperature T C the critical exponents of the magnetization of doped manganite La2/3Ca1/3Mn0.97Fe0.03O3 (LCMFO) thin films, as well as undoped La2/3Ca1/3MnO3 (LCMO). Using a T C distribution given by the intrinsic magnetic inhomogeneities in these ferromagnets enables the determination of β and δ critical exponents [corresponding to M(T) and M(H) respectively], average Curie temperature < T C > , and the T C distribution width, ΔT C. Additionally, we extracted the critical exponent η = βδ from the fits of ΔT C as a function of the external applied magnetic field. We found a value of 1.74 ± 0.09 for this exponent, close to that reported in undoped La2/3Ca1/3MnO3 thin films. Even though the substitution effects of the Mn ions by Fe affect the magnetotransport and structural properties of LCMO system, these results suggest that around T C, the magnetic phase transition, governed by the critical exponents, is similar in both magnetic systems, and belongs to the same universality class.